2012
DOI: 10.1186/1756-8935-5-12
|View full text |Cite
|
Sign up to set email alerts
|

MK3 controls Polycomb target gene expression via negative feedback on ERK

Abstract: BackgroundGene-environment interactions are mediated by epigenetic mechanisms. Polycomb Group proteins constitute part of an epigenetic cellular transcriptional memory system that is subject to dynamic modulation during differentiation. Molecular insight in processes that control dynamic chromatin association and dissociation of Polycomb repressive complexes during and beyond development is limited. We recently showed that MK3 interacts with Polycomb repressive complex 1 (PRC1). The functional relevance of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…However, PRC proteins are known to localize at active RNA polymerase 2 (POLR2) promoters in Drosophila and to interact with basal transcription factors (TF) [59]. In keeping with this notion, we recently showed that transcriptional activation at a defined PRC1-target locus did not require loss of H3K27me3 marking, but PCR1/chromatin dissociation [60]. In addition, PRC associates with splicing factors, revealing an as of yet poorly understood additional role in regulation of gene expression [61].…”
Section: Discussionmentioning
confidence: 99%
“…However, PRC proteins are known to localize at active RNA polymerase 2 (POLR2) promoters in Drosophila and to interact with basal transcription factors (TF) [59]. In keeping with this notion, we recently showed that transcriptional activation at a defined PRC1-target locus did not require loss of H3K27me3 marking, but PCR1/chromatin dissociation [60]. In addition, PRC associates with splicing factors, revealing an as of yet poorly understood additional role in regulation of gene expression [61].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that transcriptional activity persists during differentiation or physiological stress, despite increased genic H3K27me3-enrichment [33,[55][56][57]. Conversely, PRC1 was suggested to be required for gene expression in specific settings [58][59][60][61][62], illustrating the complexity of the functional interaction between PRC1 and H3K27me3 in the context of transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance, PRC1-proteins were shown to occupy promoters of actively transcribed genes and are required for POLR2A complex disassembly [41,75]. We recently showed transcriptional activation of the immediate early gene ATF3 in response to mitogenic signaling, involves release of chromatin-bound PRC1-complex members without the need for local change in promoter H3K27me3-marking [55]. PRC1-mediated transcriptional repression, instead, appears to be dependent on ubiquitylation of H2AK119, which is also involved in DNA repair [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations